The Influence of Cashback and Free Shipping Promotions on Purchase Decisions of Economics Students - Zalkha Soraya; Iftitah Resky Az-zahra J; Rajmia Sulianti; Wulandari Wulandari; Tri Ananda; Ulfatun Mutmainah; Ismar Ismar (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
The rapid growth of e-commerce platforms has transformed consumer purchasing behavior, especially among university students. This study investigates the influence of cashback and free shipping promotions on the purchase decisions of students at the Faculty of Economics and Business, Universitas Muhammadiyah Makassar. Using a quantitative approach and multiple linear regression analysis on data collected from 95 students, the study finds that free shipping promotions significantly affect purchase decisions, while cashback promotions do not show a significant individual effect. However, both promotions combined have a significant positive impact on purchase decisions. These findings provide valuable insights for e-commerce platforms to optimize promotional strategies targeting student consumers. The study contributes to the literature on digital marketing and consumer behavior in the Indonesian e-commerce context.